THE UTILIZATION OF THE GENERATIVE LEARNING MODEL IN HISTORY SUBJECT ON THE TOPIC OF THE DEVELOPMENT OF HINDU-BUDDHIST KINGDOMS IN INDONESIA AT SMAN 1 TILATANG KAMANG: Pemanfaatan Model Pembelajaran Generativ Learning Pada Mata Pelajaran Sejarah Materi Perkembangan Kerajaan Hindu-Budha Di Indonesia di SMAN 1 Tilatang Kamang - Faiza Akila; Juliandry Kurnaiawan Junaidi; Meri Erawati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to describe the planning, implementation, and challenges in applying the Generative Learning model in history learning, specifically on the topic of the Development of Hindu-Buddhist Kingdoms in Indonesia. The study is based on the observed lack of student engagement and the monotony of conventional lecture methods at SMAN 1 Tilatang Kamang. The Generative Learning model, rooted in constructivist theory, emphasizes that students build knowledge through personal experience and interaction with their environment. A qualitative approach was employed, with data collected through observation, interviews, and documentation. The research subjects included history teachers and students of class X-E5. The planning phase involved the preparation of teaching modules and student worksheets (LKPD) based on case studies related to cultural traditions with Hindu-Buddhist elements. The learning process was carried out in four stages: exploration, focusing, challenge, and application. These stages encouraged students to actively engage in group discussions, connect prior knowledge with new information, and critically analyze cultural phenomena. The findings revealed that the Generative Learning model increased student participation and understanding. This was evidenced by improved group performance, with all student groups scoring above the minimum competency criteria. However, some challenges were encountered, such as students' limited prior knowledge, difficulties in developing appropriate case studies, and time management issues during group discussions and presentations.